Adding Once-Daily Lixisenatide for Type 2 Diabetes Inadequately Controlled by Established Basal Insulin: A 24-week, randomized, placebo-controlled comparison (GetGoal-L) - Riddle, Matthew C. (American Diabetes Association, 2013)
OBJECTIVE: To examine the efficacy and safety of adding the once-daily glucagon-like peptide-1 receptor agonist (GLP-1RA) lixisenatide to established basal insulin therapy alone or together with metformin, in people with type 2 diabetes and elevated glycated hemoglobin (HbA(1c)). RESEARCH DESIGN AND METHODS: We conducted a double-blind, parallel-group, placebo-controlled trial. Patients (n = 495) with established basal insulin therapy but inadequate glycemic control were randomized to add lixisenatide 20 μg or placebo for 24 weeks. Basal insulin dosage was unchanged except to limit hypoglycemia. HbA(1c) reduction from baseline was the primary end point. RESULTS: Mean duration of diabetes was 12.5 years, duration of insulin use was 3.1 years, insulin dosage was 55 units/day, and baseline HbA(1c) was 8.4%. With lixisenatide, the placebo-corrected change of HbA(1c) from baseline was –0.4% (95% CI –0.6 to –0.2; P = 0.0002), and mean HbA(1c) at end point was 7.8%. HbA(1c) <7.0% (53 mmol/mol) was attained by more lixisenatide (28%) than placebo (12%; P < 0.0001) participants. Lixisenatide reduced plasma glucose levels after a standardized breakfast (placebo-corrected reduction, –3.8 mmol/L; P < 0.0001); seven-point glucose profiles showed a reduction persisting through the day. Reductions in body weight (placebo corrected, –1.3 kg; P < 0.0001) and insulin dosage (–3.7 units/day; P = 0.012) were greater with lixisenatide. Main adverse events (AEs) with lixisenatide were gastrointestinal. Symptomatic hypoglycemia was 28% for lixisenatide and 22% for placebo; 4 of 328 subjects (1.2%) had severe hypoglycemia with lixisenatide vs. 0 of 167 with placebo. CONCLUSIONS: By improving HbA(1c) and postprandial hyperglycemia without weight gain in type 2 diabetes with inadequate glycemic control despite stable basal insulin, lixisenatide may provide an alternative to rapid-acting insulin or other treatment options.